Porous covering compound of clay matrix and coal ashes (2018)
Here are presented the elaboration and characterization of a composite material with an atomized ceramic paste and flying ashes product of the coal combustion. The samples consist of prismatic tiles of 10x5x1 cm, formed by uniaxial pressing at 30 bars, made for mixes with a percentage weight of 90-10, 80-20, 70-30, 60-40 and 50-50, where the majority phase corresponds to the atomized ceramic paste. The drying process was conducted at room temperature for 12 hours and then in drying oven at 110 ° C for 24 hours. The sintering was carried out in gradient electric muffle at a maximum temperature of 1150 °C. According to the porous morphology and mechanical properties found for samples, this can be used as ceramic coatings with thermal isolation qualities for edifications in tropical weather like the metropolitan area of Cucuta, North Santander (Colombia)